Autonomic profile, physical activity, body mass index and academic performance of school students (2020)
The aim of this study was to analyze the autonomic modulation, physical activity, body mass index, and academic performance of preschool and school students by grade. Extracurricular physical activity, heart rate variability, body mass index, and objective and subjective academic performance were analyzed in 180 preschool and primary school students (7.91 ± 2.29 years). Significant lower heart rate and higher parasympathetic modulation were found in 10–12-year-old primary education students. The 8–9-year-old students obtained the worst results in English and in five of the subjective academic performance items. Students aged 10–12 years old presented the highest body composition values. No significant differences were found on the extracurricular physical activity by age. No correlation between autonomic profile, physical activity, and body composition with objective academic performance was found. Nerveless subjective academic performance perception of teachers presented a negative correlation with body composition and the parasympathetic modulation. School students presented an increased body mass index and parasympathetic modulation by age. Physical activity of all students, independently of the age, were lower than the official recommendations.